2022
DOI: 10.24875/j.gamo.m18000106
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia de los tumores del estroma gastrointestinal en la población mexicana. Revisión sistemática

Abstract: Introducción: Los tumores del estroma gastrointestinal representan la primera neoplasia sólida para la cual la oncogénesis ha desarrollado la primera terapia blanco molecular exitosa; Sin embargo, en México no existen estadísticas concretas sobre su prevalencia, incidencia, morbilidad o mortalidad anual; de ahí surge la necesidad de realizar un estudio que pueda proporcionar datos epidemiológicos de interés propios a nuestra población. El objetivo del presente estudio fue estimar la incidencia para los GIST en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Their incidence ranges from 4.3 -6.8 to 19 -22 cases per million (cpm) inhabitants, solely depending on the studied geographical zone 1,2 . In Latin America, the lack of data for each of the Hispanic populations is evident; nevertheless, Medina-Medina et al 3 reported a probable incidence of 9.7 cpm for Mexican population, which is higher than that reported by colleagues in the US and Canada, and showing an average age under 56 years for its diagnosis in Mexico, as well as a slight predominance of this neoplasm in females 3,4 .…”
Section: Introductionmentioning
confidence: 84%
“…Their incidence ranges from 4.3 -6.8 to 19 -22 cases per million (cpm) inhabitants, solely depending on the studied geographical zone 1,2 . In Latin America, the lack of data for each of the Hispanic populations is evident; nevertheless, Medina-Medina et al 3 reported a probable incidence of 9.7 cpm for Mexican population, which is higher than that reported by colleagues in the US and Canada, and showing an average age under 56 years for its diagnosis in Mexico, as well as a slight predominance of this neoplasm in females 3,4 .…”
Section: Introductionmentioning
confidence: 84%
“…y Europa tienen reportes de 6 a 14 casos por millón de habitantes y de 16 a 22 casos por millón de habitantes en Asia 9 . En México se registra una incidencia de 9.7 casos por millón de habitantes 10 .…”
Section: Discussionunclassified
“…Incidence rates vary worldwide, with the lowest reported in the Shanxi Province of China (4.3 cases per million inhabitants), and the highest in Shanghai, China (21.1 cases per million inhabitants) and Korea (16-22 cases per million inhabitants) [3]. In Mexico, the cumulative incidence is 9.7 cases per million inhabitants [4].…”
Section: Introductionmentioning
confidence: 99%